Magnetic Steganography Based on Wide-Field Diamond Quantum Microscopy - Yoon, Jungbae; Chung, Jugyeong; Jang, Hyunjun; Jung, Jinsu; Lee, Yuhan; Kim, Chulki; Myoung, Nojoon; Lee, Donghun (John Wiley and Sons Inc., 2025)
Magnetic steganography using wide-field quantum microscopy based on diamond nitrogen-vacancy (NV) centers is experimentally demonstrated. The method offers magnetic imaging capable of revealing concealed information otherwise invisible with conventional optical measurements. For a proof-of-principle demonstration of magnetic steganography, micrometer structures designed as pixel arts, barcodes, and QR codes are fabricated using mixtures of magnetic and non-magnetic materials: Ni and Au. Three different imaging modes based on the changes in frequency, linewidth, and contrast of the NV's electron spin resonance are compared and find that the last mode offers the best quality for reconstructing hidden magnetic images. By simultaneous driving of the NV's qutrit states with two independent microwave fields, the imaging time is expedited by a factor of three. This work shows potential applications of quantum magnetic imaging in the field of image steganography.